Identitas Budaya Masyarakat Pulau Laut dalam Makanan Tradisional Longlek - Destriyadi Destriyadi (Journal Social and Humaniora, 2024)
Cultural identity shows cultural differences from one group to another. The difference can be shown through traditional food. Not many people recognize longlek as a traditional food from Pulau Laut, Natuna. The existence of longlek is also in an unstable condition. This research aims to describe and cultural identity in longlek. This research is descriptive qualitative. The material object of this research is traditional longlek food from Pulau Laut. The formal object of this research is cultural identity. The research data sources came from longlek makers, the people of Pulau Laut, documents, activities, and perceptions concerning longlek. Data were collected using observation, interview, and literature study techniques. Informants were selected using purposive sampling method. The data analysis steps of this research are data collection, classification, interpretation, and inference. Longlek is an identity of the Pulau Laut community that is not owned by other islands in Natuna. Longlek does not only belong to the people of Pulau Laut. It should have become a communal consumption of the Natuna community. But longlek still characterizes the cultural identity of the people of Pulau Laut. Longlek is more suitable for groups that are not too crowded. This is related to its difficult material requirements. It is more suitable to be served as a special dish.